Haddon’s matrix for spectrum of road-related major injuries in rural adolescents: a case series analysis - Banerjee, Bratati; Banerjee, Rupsa (International Journal Of Community Medicine And Public Health, 2024)
Unintentional injuries in children pose public health threat that often leads to serious consequences in the child and the family, especially in case of major injuries. Prevention strategies need to be worked out for all injuries, particularly for major injuries which cause considerable disability and mortality. We present three road-related major injury events which had occurred during the entire period of a larger study, which have been analyzed using the Haddon’s matrix through an epidemiological tetrad model involving host, vector, physical environment and socio-economic environment. Intervention strategies for prevention of similar injuries in future have been outlined at various time points for each case, as well as general measures, in various levels of care. Of the three major road-related injury cases (12 years, female; 17 years, female; and 17 years, male), two were automobile accidents in 17 years old adolescents and one was a case of injury of a 12-year-old girl due to fall on road. Risk factors were present in all three cases related to host, vector, physical environment and socio-economic environment. Strategies for prevention have been outlined at various time points i.e. pre-event, event, post-event at various levels for each case, as well as intervention strategies that can be implemented in general by the individual, family, community including panchayat, and both State and National governments. All major road-related injuries and their complications that occurred in subjects of the present study could have been prevented by taking responsibility at various levels.